2015
DOI: 10.1161/circulationaha.114.012066
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogenic Therapy With Finasteride Attenuates Cardiac Hypertrophy and Left Ventricular Dysfunction

Abstract: A pproximately 5 million Americans have chronic heart failure. 1 The most common causes for the development of chronic heart failure are chronic arterial hypertension, myocardial hypertrophy, and previous myocardial infarction. 1 The progression of heart failure is driven by pathological ventricular remodeling processes, which mainly involve cardiomyocyte hypertrophy, myocardial fibrosis, and profound changes in gene expression that together lead to left ventricular dilation and systolic, and diastolic dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 47 publications
1
49
0
3
Order By: Relevance
“…Support for this possibility is provided by previous studies in which antiandrogenic treatment attenuated cardiac hypertrophy. 110 , 111 …”
Section: Discussionmentioning
confidence: 99%
“…Support for this possibility is provided by previous studies in which antiandrogenic treatment attenuated cardiac hypertrophy. 110 , 111 …”
Section: Discussionmentioning
confidence: 99%
“…Constriction of the transverse aortic arch (TAC) was performed in 8-to 10-week-old gene-deleted or WT mice around a 25-gauge needle, as previously described. 19,20 For the mice after adeno-associated virus serotype 9 (AAV9) injection, TAC was conducted using a 26-gauge needle. All procedures involving the use and care of animals were performed according to the Guide for the Care and Use of Laboratory Animals published by the National Research Council (NIH Publication No.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…In observational studies, Shores et al have shown that shown that high DHT is associated with increased cardiovascular events (66) and increased incident ischemic stroke (65). Interestingly, Zwadlo et al (96) have shown that cardiac expression of 5␣-reductase is markedly increased in humans with heart failure and in a mouse aortic constriction model of heart failure. In a mouse model, treatment with finasteride attenuated cardiac hypertrophy and improved left ventricular function.…”
Section: E1038 Safety and Effectiveness Of Injected Testosteronementioning
confidence: 99%